Unmasking the global journey: investigation of SARS-CoV-2 variants of interest across various regions through whole-genome and phylogenetic analysis - Surendran, Yocyny; Vityashri, Parameswaran; Juhari, Nazwin Shahirah; Thilakavathy, Karuppiah; Chenglong, Xiong; Joseph, Narcisse (Brieflands, 2024)
Background: The prolonged course of the Coronavirus Disease 2019 (COVID-19) pandemic and the virus's high mutation rate have sparked widespread interest in studying Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Research has shown that SARS-CoV-2 has evolved into numerous variants since its discovery. Objectives: This study aimed to investigate the differences in SARS-CoV-2 Variants of Interest (VOI) and Variants of Concern (VOC) from different geographical regions through phylogenetic analysis and mutational analysis. Methods: A total of 700 SARS-CoV-2 whole-genome sequences were retrieved from the GISAID database from January 1, 2021, to December 31, 2021. These sequences were aligned with the reference sequence (NC_045512) using Clustal Omega version 1.2.4. A phylogenetic tree was constructed using the IQ-TREE web server and visualized using ItoL. Results: The results revealed a fully resolved maximum likelihood tree with statistical support based on bootstrap values. The analysis demonstrated that Delta variant sequences clustered separately from other VOIs, VOCs, and outgroups. The shorter topology of the Delta variant showed that Africa branched away, similar to the Lambda and Gamma variants. Additionally, structural analysis identified three primarily uniform clusters in Europe, North America, and South America, which corresponded to the sister relationships observed in Clades 1, 2, and 7 topologies. These evolutionary trees were later linked to mutations in the spike, nucleocapsid, and nsp3 proteins, which displayed a high number of mutations. Conclusions: This study provides new insights into the evolving mutations of SARS-CoV-2 VOIs and VOCs across different regions of the world, contributing to our understanding of viral pathogenicity.